State Bar of California Annual Meeting Held at Century Plaza Hotel - Watkins, Howard::::::::: (1987)
?, Robert Marshall-Andrews.?, State Bar President Anthony Murray, James Brosnahan, Robert Aiken, Alvin Goldstein, and Desmond Fennell